Методика оценки воздействия региональной экономической интеграции на привлечение прямых иностранных инвестиций - Турлай, И.С. (Изд-во КарГУ., 2012)
Мақалада елдер экономикасына ынтымақтастық топтарына кіргенге дейін жəне кейін түсетін шетелдік тұра инвестициялардың (ШТИ) өсу қарқынын талдауға негізделген аймақтық экономикалық бірігудің ШТИ тартуына əсері анықтаудың əдістемесі берілген. Бұл əдістемені қолдану жалпы ШТИ тартуда бірігудің оң əсерін белгіледі. Ұсынылып отырған əдістеме кейінгі зерттеулер өткізгенде аймақтық кірігудің инвестициялық мəнін бағалауда қажет. The article describes and substantiates the methodology of determining the impact of regional economic integration on foreign direct investment (FDI) which presupposes the examination of dynamics of FDI inflows into the economy of countries before and after their entry to the integration groupings, as well as the construction of two main types of investment econometric models with the regional integration factors included. The results of applying this methodology in the relevant studies generally indicate the positive impact of integration on FDI. The considered methodology can be used in further studies for the assessment of the investment significance of regional integration among other factors of the dynamics of FDI attraction to specific countries and groupings.
Keywords: развития современной мировой экономики; иностранная инвестиция; Методика оценки; воздействия региональной экономической интеграции